Pertumbuhan Vegetatif Talas Satoimo dan Kultivar Lokal pada Dosis Pupuk Nitrogen yang Berbeda - Yulian, Yulian; Turmudi, Edhi; Hindarto, Kanang S.; Bustamam, Hendri; Hutajulu, Juwita Noventina (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
Taro (Colocasia esculenta L. Schott) is a plant that has an excellent economic and healthy value, as well as a great potential development of Bengkulu coastal area. That is because taro has wide adaptability, and can be consumed both as a staple food and healthy food alternative. This research was conducted to study the vegetative growth of two cultivars of taro given four different doses of nitrogen. This study applied a Randomized Complete Block Design (RCBD) with two factors. The first factor was the cultivar of taro consisted of two levels, namely Taro Satoimo (T1) and the Taro Local (T2). The second factor was the doses of nitrogen fertilizer which consisted of four levels namely: N0 = 0 kg / ha (control), N1 = 50 kg / ha (2.6 g, N2 = 100 kg / ha, and N3 = 150 kg / ha. Thus, obtained eight treatment combinations. Each treatment was repeated three times to get 24 plots. The results showed that based on increased vegetative growth, the cultivar Satoimo has a faster response than local cultivar. Satoimo has demonstrated another advantage because it produced some leaves and number new shoot. The best dose of nitrogen fertilizer on the vegetative growth of taro in the coastal area of Bengkulu is 150 kg/ha.